Postmodern Feminist And Postcolonial Currents In Contemporary Japanese Culture : a Reading Of Murakami Haruki, Yoshimoto Banana, Yoshimoto Takaaki And Karatani Kojin. - Murakami, Fuminobu (Taylor & Francis Ltd., 2005)
Using the Euro-American theoretical framework of postmodernism, feminism and post-colonialism, this book analyses the fictional and critical work of four contemporary Japanese writers - Murakami Haruki, Yoshimoto Banana, Yoshimoto Takaaki and Karatani Kojin. This book is useful for those studying Japanese literature, and Japanese studies.